The Kindergarten Hotspot: Literacy Skill Convergence Between Boston Prekindergarten Enrollees and Nonenrollees. Issue 2 (3rd January 2021) - Weiland, Christina; Unterman, Rebecca; Shapiro, Anna
Abstract : Preschool improves children's kindergarten readiness, but the cognitive outcomes of preschool enrollees and nonenrollees tend to converge partially or fully in elementary school. In older programs, most of this convergence occurs in kindergarten (Li et al., 2016), but evidence from today's programs is sparse. Using data on 4, 971 children who applied to the Boston Public School Prekindergarten program and a quasi‐experimental approach, we examine convergence in kindergarten through third grade (K‐3) literacy outcomes of prekindergarten enrollees and nonenrollees. Consistent with previous literature, most of the convergence in K‐3 literacy outcomes occurred in kindergarten. Our findings suggest that detailed investigations into the kindergarten teaching and learning context may be particularly important for solving the widely noted preschool convergence pattern.